Identification of most damaging nsSNPs in human CCR6 gene: In silico analyses. (31st July 2019) - Akhtar, Mehran; Jamal, Tazkira; Jamal, Hina; Din, Jalal Ud; Jamal, Muhsin; Arif, Muhammad; Arshad, Maria; Jalil, Fazal
Abstract: Single nucleotide polymorphisms in CCR6 (C–C chemokine receptor type 6) gene have been found to be the possible cause of many diseases like rheumatoid arthritis, psoriasis, lupus nephritis and systemic sclerosis and other autoimmune diseases. Therefore, identification of structurally and functionally important polymorphisms in CCR6 is important in order to study its potential malfunctioning and discovering therapeutic targets. Several bioinformatics tools were used to identify most damaging nsSNPs that might be vital for CCR6 structure and function. The in silico tools included PROVEAN, SIFT, SNP&GO and PolyPhen2 followed by I‐Mutant MutPred and ConSurf. Phyre2 and I‐TASSER were used for protein 3‐D Modelling while gene–gene interaction was predicted by STRING and GeneMANIA. Our study suggested that three nsSNPs rs1376162684, rs751102128 and rs1185426631 are the most damaging in CCR6 gene while 7 missense SNPs rs1438637216, rs139697820, rs768420505, rs1282264186, rs1394647982, rs769360638 and rs1263402382 are found to revert into stop codons. Prediction of post‐transcriptional modifications highlighted the significance of rs1376162684 because it effected potential phosphorylation site. Gene–gene interactions showed relation of CCR6 with other genes depicting its importance in several pathways and co‐expressions. In future, studying diseases related to CCR6 should include investigation of these 10 nsSNPs. Being the first of its type, this study also proposes future perspectives that will help in precision medicines. For such purposes, CCR6 proteins from patients of autoimmune diseases should be explored. Animal models can also be of significance find out the effects of CCR6 in diseases.